Multiple non-symmetrical lipomatosis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2017)
Skin lipomatoses are rare diseases characterized by excessive and progressive benign proliferation of fat cells not enclosed in a capsule unlike lipoma. When they do not compress vital structures they have an exclusive esthetic meaning. Depending on the distribution, a symmetrical lipomatosis is distinguished, which is mainly located around the neck and the scapular girdle and may be associated with lipid metabolism alterations; moreover, there is a non-symmetrical lipomatosis, often familiar and transmitted by an autosomal dominant trait, which is usually not associated with lipids metabolic disturbances. Once excluded lipid metabolism alterations, lipomatosis treatment is essentially surgical and has only esthetic purpose: it is possible to use lipectomy (2), which can be followed by relapse, or liposuction (1).